EFEKTTVITAS PENYELENGGARAAN PROGRAM KURSUS PARA PROFESI (KPP) TERHADAP PENGURANGAN ANGKA PENGANGGURAN DIPROPINSI DAERAHISTIMEWA YOGYAKARTA - Hiryanto , Lutfi Wibawa (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2010)
This research is to explore the information about; 1 How much the environment in which learning support programs providing KPP in Daerah Istimewa Yogyakarta. Fabric cooperation partner organizations organizer unit KPP with relevant agencies to support the implementation of KPP programs, residents learn the characteristics KPP programs in Daerah Istimewa Yogyakarta, the characteristics of educators KPP programs in the energy characteristics of the Special Region of KPP program, the availability of facilities and educational infrastructure at partner institutions organizers KPP program in Daerah Istimewa Yogyakarta 2). Implementation of learning in the program organizers partner agencies in Daerah Istimewa Yogyakarta of KPP. Include factors that support the implementation of learning programs at partner institutions KPP program organizers, the factors that hinder the implementation of learning programs at partner institutions KPP program providers in Daerah Istimewa Yogyakarta, 3) benefits that have been obtained after a citizen study KPP program and how many graduates of the program KPP is absorbed in the business world. This research is an evaluation study with descriptive qualitative approach. Subject of this research is the program organizer KPP, Instructor program, residents or students studying and working partner of LPK Desanta Yogyakarta, LPK Bina Karya and LPK MaCell Education Center. Research conducted in may until September 2009, techniques of data collection is done by the method of observation, interviews and documentation. Engineering data analysis is done by stages of data reduction, data display phase and stage of collection and verification decisions. Validity of the data is carried out through trianggulasi source. The results showed: Organization of KPP either program conducted by the LPK Desanta Yogyakarta, LPK Bina Karya and LPK MaCell Educational Center begins with the identification of needs, which include labor, potential learners and educators, KPP program held for 3 months with the program specifically designed, with a comparison of theory and practice, 30: 70 as well as apprenticeship and placement of graduates, learning program specifically designed for KPP programs, supporting factor of this program is the support from government funds, available facilities and infrastructure, educators, and motivation of learners, Inhibiting factors derived from variations in learners' backgrounds, delays in fundraising. Viewed from the graduate program organized by KPP 3 LPK block that received funding grants from the department of Education, more than 80% absorbed in the world of work, general KPP program is very beneficial for the working world as well as to reduce unemployment. Keywords: KPP Programs, Reduce Unemployment